2018
DOI: 10.2215/cjn.07050717
|View full text |Cite
|
Sign up to set email alerts
|

Serum Bicarbonate Concentration and Cognitive Function in Hypertensive Adults

Abstract: In a large cohort of hypertensive adults, higher serum bicarbonate levels were independently associated with better global cognitive and executive performance. (ClinicalTrials.gov: NCT01206062).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Diminished serum IGF-1 in patients with renal failure has been linked to a higher rate of mortality [ 46 ]. In addition, acidosis has been linked to altered insulin sensitivity [ 47 ], skeletal demineralization, nephrolithiasis, and, in hypertensive adults, cognitive impairment [ 48 ]. These observations further emphasize the critical role of active kidney compensation to defend the systemic acid-base balance in the setting of the acidogenic diet.…”
Section: Maladaptations To the Modern Diet And Health Implicationsmentioning
confidence: 99%
“…Diminished serum IGF-1 in patients with renal failure has been linked to a higher rate of mortality [ 46 ]. In addition, acidosis has been linked to altered insulin sensitivity [ 47 ], skeletal demineralization, nephrolithiasis, and, in hypertensive adults, cognitive impairment [ 48 ]. These observations further emphasize the critical role of active kidney compensation to defend the systemic acid-base balance in the setting of the acidogenic diet.…”
Section: Maladaptations To the Modern Diet And Health Implicationsmentioning
confidence: 99%
“…A systematic review found that both global cognitive function and language function were particularly impaired in CKD (6). However, this study by Dobre et al (10) found that lower bicarbonate was associated with lower scores on both global and executive function tests, but there was no association seen with language domains or other domains. The exact domains potentially affected by the shared issues of CKD and acidosis are, therefore, still unknown.…”
mentioning
confidence: 66%
“…In summary, the study by Dobre et al (10) adds another piece of evidence that acidosis is harmful. In addition to its previously studied associations with mortality, kidney disease progression, and other clinical outcomes, we can now add cognitive impairment to the areas that acidosis likely affects.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Our results extend those of previous papers reporting that lowered bicarbonate levels may be associated with lower performance on cognitive tests including cognitive or executive impairments. (54,55) For example, in a large cohort of individuals with hypertension, higher serum bicarbonate levels were associated with better global cognitive and executive functioning, but not with memory. (54) The latter authors computed that a decrease of 1 mEq/L in bicarbonate had the same impact on global cognitive functioning as being 4.3 months older.…”
Section: Discussionmentioning
confidence: 99%